Effects of isoxsuprine hydrochloride on electrocardiographic and trace element status in sheeps - Vural, Handan Aydin; KOENHEMSİ, Lora; Gonul, Remzi; Yardibi, Hasret Demircan; GÜLYAŞAR, TEVFİK; OR, Mehmet Erman; Hosturk, Gulhan Turkay; Barutcu, Bora; Balci, Huriye (My University, 2016)
Objective: To study the effect of isoxsuprine hydrochloride on the ischaemic electrocardiographic change and trace element status in sheep.